Geometry of nonholonomic complexes NGr(1, 4, 4) - Navickis, Kazimieras (Lietuvos matematikos rinkinys, 2003)
In this article intrinsic normalizations of a nonholonomic complexes NGr( 1, 4, 4) in projective space P4 is constructed in an invariant form.